2014
DOI: 10.3747/co.21.1973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Osteosarcoma Patients Treated with High-Dose Methotrexate-Free Neoadjuvant Chemotherapy

Abstract: (1) Objective: High-dose methotrexate (hdmtx) is a common therapeutic agent in the treatment of osteosarcoma. However, hdmtx is highly toxic and requires complex pharmacokinetic monitoring and leucovorin rescue. Thus, alternative therapeutic strategies are necessary. Here, we analyzed the clinical efficacy of a dia regimen (cisplatin–ifosfamide–doxorubicin) to evaluate its potential as an alternative to hdmtx–based therapy. (2) Methods: Patients received 12 cycles of chemotherapy administered over 2 years (2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
(29 reference statements)
1
26
0
Order By: Relevance
“…This adds credence to the possibility that large tumor size in the vast majority of our patients (90% >8 cms; 25% amputation rate) could have impacted on the poorer outcomes . In the current era of limb salvage, assuming amputations to be a surrogate marker for tumor size; Table depicts the outcomes of non‐metastatic patients with high grade osteosarcoma (treated with three drugs or more, with/without methotrexate) in series published within the last 10 years …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This adds credence to the possibility that large tumor size in the vast majority of our patients (90% >8 cms; 25% amputation rate) could have impacted on the poorer outcomes . In the current era of limb salvage, assuming amputations to be a surrogate marker for tumor size; Table depicts the outcomes of non‐metastatic patients with high grade osteosarcoma (treated with three drugs or more, with/without methotrexate) in series published within the last 10 years …”
Section: Discussionmentioning
confidence: 87%
“…Xu et al and Assi et al demonstrated an overall survival of 62% and 69%, respectively in their series without HDMTX . Both these series had limb salvage rates in excess of 90% (possibly a reflection of smaller tumors).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Chemotherapy has dramatically changed the cure rate of malignant bone tumors [6,[17][18][19]. Since the introduction of effective neo-adjuvant chemotherapy in the 1980s, more than 80% of patients with osteosarcoma of an extremity have been considered candidates for limb-salvage surgery, and that increased the trend of using the endoproshtesis for limb-salvage surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the history, before the 1970s, the amputation and knee disarticulation were the main treatment for primary malignant bone tumors around the knee [1,2]. With better understanding of the biological behavior of musculoskeletal tumors, application of effective neo-adjuvant and adjuvant therapy and the development of bone defect reconstruction, 75% of malignant tumors around the knee can be safely resected through some limb salvage procedures [6][7][8][9]. In this paper, we investigate the clinical and functional outcomes of limb salvage operations for bone tumors of the knee.…”
mentioning
confidence: 99%